“Meshing into One”: An Assessment of Law Enforcement and Clinician Perspectives on Professional Roles and the Embedded Co-Responder Model - Crichlow, Vaughn J. (Criminal justice and behavior, 2025)
In situations where mental health and social services are needed, aggressive law enforcement responses can be harmful. Increasing knowledge in this area has led to the creation of programs involving collaborations between police and mental health professionals. Embedded co-responder programs, also known as police-social work programs, in which clinicians are physically located at police departments, have emerged as an alternative model for responding to the mental health needs of community members in crisis and the threat of violence. This qualitative study examines the perspectives of detectives and clinicians who serve on an embedded co-responder team at a large police agency in Florida. The study explores perspectives on the professional roles of police and clinicians and the perceived impact of the co-responder program, also known as the Targeted Violence Unit, in connecting individuals to services and preventing crime. Broader implications for justice and mental health partnerships are discussed.